Peran Orangtua Terhadap Pendidikan Islam Anak Sejak Dini - Faris Jibran Farruqi; Hazkiyal Abdillah; Siti Halimah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Early Islamic education significantly influences the development of children's character, ethics, and spirituality. The role of parents in facilitating Islamic education during this stage greatly impacts children's growth. This study aims to examine how parents contribute to the implementation of Islamic education from a young age and the effect it has on instilling religious values in children. The research employs a qualitative methodology, utilizing detailed interviews and observations of parents with young children. The results indicate that parents are instrumental in imparting Islamic teachings through their parenting style, the integration of religious values into everyday life, and overseeing their children's religious practices. Nevertheless, this involvement is affected by various factors, such as parents' comprehension of Islamic education, time limitations, and the availability of educational resources.